(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يجسد الإفصاح في المحاسبة عملية تقديم المعلومات الضرورية والكافية عن الوحدات الاقتصادية للأطراف ذات المصالح الحالية أو المستقبلية بتلك الوحدات. تهدف هذه الدراسة إلى قياس مستوى الإفصاح الاختياري في التقارير المالية للشركات المساهمة المسجلة في سوق دمشق للأوراق المالية وذلك عبر اختبار قائمة مكونة من ستين عنصراً تمثل العناصر الأساسية للإفصاح الاختياري بالتطبيق على التقارير السنوية المنشورة عام 2009 لخمس عشرة شركة من الشركات المساهمة السورية المسجلة. استخدم المنهج الإيجابي في قياس مستوى التباين في الإفصاح الاختياري، وتحديد حجمه ونوعيته في العينة المدروسة، وقد بينت نتائج البحث أنه بالرغم من وجود تباين في حجم ونوعية الإفصاح الاختياري إلا أن هناك اهتماماً ملحوظاً به من قبل الشركات، ورغبةً بتزويد الأطراف المهتمة بمعلومات إضافية عن تلك التي يفرضها الإفصاح الإلزامي. Disclosure is used in accountancy as an expression of presenting necessary& sufficient information about the economic units to the present and potential stakeholders. The purpose of this study is to measure the level of the voluntary disclosure in the annual reports of the Syrian joint stock companies that listed in Damascus Securities Exchange. The Study have tested a checklist of 60 points representing the basic elements of the voluntary disclosure applied on the 2009 annual reports of 15 Syrian joint stock listed companies. The positive approach is used to measure the variance of the voluntary disclosure and defined its size and quality in the studied sample. The results show that although there is difference in the size and quality of the voluntary disclosure, but the companies have significant interest and serious desire to provide all interested parties with additional information on those imposed by mandatory disclosure.